Challenges for national clean air policy - Comes, Tina; Doll, Claus; Fröhling, Magnus; Hiete, Michael; Ilsen, Rebecca; Krail, Michael (Ökologisches Wirtschaften - Fachzeitschrift, 2010)
Clean air policy faces not only the classical problems like multi-pollutant aspects but also complex consequences of instruments on production costs, competition and consumption. A new model can support clean air policy in Germany.
Keywords: Clean air policy